MANAJEMEN STRATEGI RUMAH SAKIT DALAM ERA JKN : STUDI LITERATUR INTEGRASI BALANCED SCORECARD, LEAN HOSPITAL, DAN ADAPTASI DIGITAL MENUJU TRANSFORMASI KRIS 2025 - Bambang Subekti; Nani Asrini; H. Purwadhi; Yani Restiani Widjaja (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2026)
The hospital sector in Indonesia is currently facing significant challenges due to the dynamic policies of the National Health Insurance (JKN) and the mandatory implementation of Standard Inpatient Classes (KRIS), scheduled to be effective in July 2025. A crucial issue arises from the disparity between INA-CBGs tariffs and operational costs, demanding high efficiency without degrading service quality. Through a Systematic Literature Review (SLR) of 25 recent references (2020-2025), this study formulates an integration between the Balanced Scorecard (BSC) and Lean Management. Findings indicate that BSC-based digitalization can boost patient satisfaction by up to 96%, while Lean methods successfully eliminate operational waste by up to 70%. The sustainability of hospitals heavily depends on organizational agility, digital transformation, and adaptive leadership.